The Effect of Synthetic Cannabinoids on P-Wave Dispersion: An Observational Study - Aydin Sunbul, Esra (Med Princ Pract, 2016)
OBJECTIVE: The aim of this study was to investigate the effect of synthetic cannabinoids (SC) on P-wave dispersion (PD) in patients who consume SC. MATERIALS AND METHODS: The study population included 72 patients who consumed SC and 36 age- and sex-matched healthy controls. The severity of addiction was detected using the addiction profile index (BAPI). The PD was measured by 12-lead ECG obtained upon admission to hospital. Statistical analyses were performed using the SPSS v20.0 statistical software package. RESULTS: The mean age of the patients and controls was 26.9 ± 7.0 and 26.3 ± 6.5 years, respectively. Mean duration of SC consumption was 1.7 ± 0.7 years. Mean BAPI score of patients who consumed SC was 12.8 ± 3.4. Patients who consumed SC had a significantly higher PD value than controls (37.7 ± 11.5 vs. 30.6 ± 6.4 ms, p < 0.001). The BAPI score was significantly correlated with PD value (r = 0.675, p < 0.001). In the linear regression model that included PD value, age and heart rate, PD value was significantly and independently correlated with BAPI score (r(2) of the model = 0.339; p < 0.001). CONCLUSIONS: In this study, patients who consumed SC had significantly higher PD values than controls, and the BAPI score correlated with the PD value. Hence SC consumption could lead to an increased risk of cardiovascular disease through prolonged PD. We recommend the use of the simple and inexpensive ECG to assess cardiovascular risk in patients who consume SC.